PEMBERDAYAAN MASYARAKAT DALAM KEPEMILIKAN JAMBAN KELUARGA DI DESA TALANG BOSENG WILAYAH PUSKESMAS SIDODADI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Widada, Agus; Jubaidi, Jubaidi; Mualim, Mualim; Marwanto, Andriana; Oktavia, Dina (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Efforts to improve hygiene behavior and increase access to sanitation continue to be developed. One of the applications of the Community Led Total Sanitation (CLTS) concept, CLTS is a concept with a promotion approach by facilitating the community to apply good environmental sanitation with a focus on not defecating in the open. Based on the 2019 annual report Health Center, the incidence of diarrhea ranks second in environmental-based diseases with 111 cases. The high prevalence of diarrhea is partly due to the lack of access to clean water, as much as 27.4% of clean water facilities/dug wells do not meet the requirements. As many as 35% of households still defecate in the open. The process of implementing community service activities in the framework of open defecation-free villages in Talang Boseng Village Working Area of ​​the Sidodadi Health Center, Pondok Kelapa District, Central Bengkulu Regency, namely using a combination of triggering and providing stimulants for the construction of family latrines carried out by the Community Service Team from the Bengkulu Ministry of Health Polytechnic, Sidodadi Health Center, Sidodadi Village Officials, and the Sidodadi community who do not yet have or who have latrines that do not meet health requirements.